2008
DOI: 10.1007/s10964-008-9280-0
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Early Adolescents’ Depressive Symptoms, Aggression and Perceived Parental Rejection: A Four-Year Community Study

Abstract: This study of early adolescents from the general population examined the direction of effects adolescents' depressive symptoms, aggression, and perceived parental rejection have on one another in a longitudinal study. Over a four-year period, data were collected yearly from 940 early adolescents (50.6% boys and 49.4% girls) who completed self-report questionnaires of depressive symptoms, aggressive behaviors, and perceived parental rejection. The longitudinal relationships of adolescent reported depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 45 publications
(51 reference statements)
6
62
0
1
Order By: Relevance
“…There was a relatively small unidirectional effect of delinquency on depression for boys, whereas bidirectional effects were found for girls (Wiesner 2003). In contrast, others suggest the opposite, that the similar developmental patterns of problems are found for girls as have been found for boys (Gorman-Smith and Loeber 2005;Hale et al 2008;Vieno et al 2008). There are no sex differences in comorbidity (Ritakallio et al 2008) or in cross-lagged associations between the two domains (Overbeek et al 2001).…”
Section: Sex Differencesmentioning
confidence: 90%
See 1 more Smart Citation
“…There was a relatively small unidirectional effect of delinquency on depression for boys, whereas bidirectional effects were found for girls (Wiesner 2003). In contrast, others suggest the opposite, that the similar developmental patterns of problems are found for girls as have been found for boys (Gorman-Smith and Loeber 2005;Hale et al 2008;Vieno et al 2008). There are no sex differences in comorbidity (Ritakallio et al 2008) or in cross-lagged associations between the two domains (Overbeek et al 2001).…”
Section: Sex Differencesmentioning
confidence: 90%
“…Masten et al (2005), for example, found that externalizing behaviors undermined academic achievement, which, in turn, increased risk for later internalizing symptoms. Similarly, Hale et al (2008) demonstrated that adolescents' depressive symptoms (mean age = 12.4 at the first wave) affected perceived parental rejection and, in turn, affected adolescents' aggression over a 4-years period. These results suggest that one domain of problem ''spills over'' to influence functioning in the other domain of problem via third variables including academic achievement and parental rejection.…”
Section: Directional and Third Variable Explanations Of Co-occurring mentioning
confidence: 94%
“…Parenting continues to influence the child's adjustment over the course of the child's life, from infancy on (Bornstein 2002). More specifically, in childhood and adolescence, parenting is related to externalizing and internalizing problems as depression (Hale et al 2008;Steinberg 2001). In addition, the influence of parenting on adolescent adjustment is in complex interplay with other factors such as heritability, child characteristics, and peer influences.…”
Section: Discussionmentioning
confidence: 99%
“…Both parental depression and low quality parenting are associated with higher rates of adolescent depressive symptoms (Bureau et al 2009;Kaslow et al 1994;Leis and Mendelson 2010;Repetti et al 2002). In general, high parental rejection and control are associated with higher rates of depression in adolescents (Hale et al 2008;McLeod et al 2007). Conversely, good quality parenting, high levels of perceived parental warmth, low perceived parental control, and adequate emotional involvement are related to fewer depressive feelings in children (Brennan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Reliability and construct validity have been shown to be strong in adolescent samples (e.g., Hale, Vandervalk, Akse, & Meeus, 2008). The questionnaire consists of the subscales direct aggression, indirect aggression and withdrawal, but in this study only direct aggression is taken into account.…”
Section: Conamore Measuresmentioning
confidence: 99%